Developing the Instrument of Non-Cognitive Skill Assessment for Science at Junior High School Grade VII: A Conceptual Review - Nur Agastya, Widha; Devi Triana, Dinny; Haribowo, Herwindo (KnE Social Sciences, 2020)
This research is a qualitative study based on the previous research, which will, apply and adapt the earlier findings to Indonesia’s education system. The particular focus of this study is the non-cognitive skills needed for the study of science subjects at junior high school grade VII, namely: accurateness; perseverance; conscientiousness; responsibility; critical thinking; innovation; open mindedness; sensitivity; empathy; and environmental awareness. This is based on non-cognitive skill construction involving: individual character; emotion; habit; and process. Those aspects can be developed into the syllabus and lesson plans, both evaluating and developing the students’ non-cognitive skills. Keywords: developing instrument, cognitive skill, non-cognitive skill, science, junior high school